Analysis of the Shooting skill on goal in the group stage Egypt 2019 - oussama merniz; saoudi ayoub (sports creativity, 2025)
The purpose of the study was to determine the number of shots on goal for all teams participating in the tournament, according to the playing positions, the shooting zones, also the most used body parts and finally the precision, in addition to know the proportion of goals. The researcher chose all teams participating in the Africa Cup 2019 Egypt as a sample of the study, and also used the descriptive method because of their relevance to the nature of the study, we used the videos recorded the 36 games of the first round of the tournament, in addition to the scientific observation form as a tool for collecting numbers and statistics. The most important results indicated that most of the shots were from the play positions and the penalty area and that most shots were out of bounds.